Different vertical heat transport induced by submesoscale motions in the shelf and open sea of the northwestern South China Sea - Pan, Hao; Qiu, Chunhua; Liang, Hong; Zou, Liwei; Zhang, Ziqi; He, Benjun (Frontiers in Marine Science, 2023)
Submesoscale currents are known to be associated with strong vertical velocities (O (10) m/day), regulating the redistributions of energy and matter balances. The northern South China Sea (SCS) is fulfilled with submesoscale motions, which might induce strong vertical heat transport (VHT). We set up a 1-km horizontal resolution Massachusetts Institute of Technology General Circulation Model (MITgcm) to study the seasonal variations in submesoscale vertical heat transport in shelf region and open sea. Spectrum analysis shows that the spatial scale separating submesoscale and mesoscale motions are 14 km and 30 km for shelf and open region, respectively. The submesoscale VHT in the shelf region is one order larger than that in the open ocean.The former has the largest value in summer and winter, which might be induced by summer upwelling and winter downwelling, while the latter is strongest in winter and weakest in summer in open region. The submesoscale VHT also appears intra-seasonal variations, and might be attributed to the disturbances of tropical cyclones and submesoscale eddies' life stage. The submesoscale VHT is strongest in the pregeneration phase of the eddies, and the maximum VHT belt has an entrainment type at the developing and mature stages. The chlorophyll-a concentration also has the same temporal variation as the different life-stage of eddies. This study provides local VHT induced by submesoscale motions, which is expected to improve our understanding on submesoscale air-sea interaction and their biological effects.